PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD - ., Ni Putu Inda Kristarini; ., Drs. I Made Suarjana, M.Pd; ., Dra. Ni Wayan Arini,M.Pd (Universitas Pendidikan Ganesha, 2017)
Penelitian ini bertujuan untuk mengetahui perbedaan yang signifikan hasil belajar IPS antara kelompok siswa yang dibelajarkan dengan menggunakan model pembelajaran talking stick dan kelompok siswa yang dibelajarkan tidak menggunakan model pembelajaran talking stick pada siswa kelas V SD di Gugus IV Rama Kecamatan Jembrana Kabupaten Jembrana Tahun Pelajaran 2016/2017. Populasi penelitian ini adalah seluruh kelompok siswa kelas V SD di Gugus IV Rama Kecamatan Jembrana tahun pelajaran 2016/2017 yang berjumlah 218 orang. Sampel penelitian ini adalah kelompok siswa kelas V SD Negeri 1 Pendem yang berjumlah 33 orang dan kelas V SD Negeri 2 Pendem yang berjumlah 36 orang. Data hasil belajar IPS siswa dikumpulkan dengan tes berbentuk pilihan ganda. Data yang dikumpulkan dianalisis menggunakan analisis statistik deskriptif dan analisis statistik inferensial (uji-t). Hasil penelitian ini menunjukkan bahwa terdapat perbedaan hasil belajar IPS yang signifikan antara siswa yang dibelajarkan dengan model talking stick dan dan siswa yang dibelajarkan tidak menggunakan model talking stick. Hal ini ditunjukkan oleh thitung (3,70) > ttabel (1,99) serta perbandingan perhitungan rata-rata hasil belajar IPS siswa yang dibelajarkan menggunakan model talking stick lebih besar dari rata-rata hasil belajar IPS siswa yang dibelajarkan tidak menggunakan model talking stick yaitu 18,72 > 14,09. Hal ini berarti bahwa penggunaan model pembelajaran talking stick berpengaruh terhadap hasil belajar IPS siswa kelas V SD di Gugus IV Rama Kecamatan Jembrana tahun pelajaran 2016/2017. Kata Kunci : hasil belajar, IPS, talking stick. This study aimed to find out the significant differences of students’ outcomes in learning social studies (IPS) between group of students who were taught by using talking stick teaching method and group of students who were not taught by using talking stick teaching model of the fifth grade students of elementary school at Gugus IV Rama, Jembrana Sub-district Jembrana District in academic year 2016/2017. The population of this study is 128 fifth grade students of elementary school at Gugus IV Rama Jembrana District in the academic year 2016/2017. The sample of this study is 33 fifth grade students of SD Negeri 1 Pendem and 36 fifth grade students of SD Negeri 2 Pendem. The data of student’s learning outcomes were collected by using multiple choice test. The, the gained data were analyzed by using descriptive statistical analysis an inferential statistical analysis (t-test). The results of this study indicate that there are significant differences on students outcomes in learning social studies between students who were taught by using talking stick teaching method and students who are not taught by using talking stick teaching method. It was indicated by tcount (3,70) > ttable (1,99) and the comparison of mean score of students who are taught using talking stick teaching method is higher than the mean score of students who are not taught by using the talking stick model, that is 18,72 > 14,09. Therefore, it can be concluded that the use of talking stick as a teaching method has an effect on the students outcomes in learning social studies of the fifth grade students of elementary school at Gugus IV Rama Jembrana sub-disrict in the academic year 2016/2017. keyword : learning outcomes, IPS, talking stick.